2007
DOI: 10.1590/s0102-05362007000100016
|View full text |Cite
|
Sign up to set email alerts
|

Produção de minitubérculos básicos de batata em três sistemas hidropônicos

Abstract: Potato basic minitubers production in three hydroponic systemsThe objective of this work was to evaluate the production of potato basic minitubers in three hydroponic systems: aeroponic, DFT (deep flow technique) and NFT (nutrient film technique), using cultivars Agata and Monalisa. The experiment was carried out under protected cultivation, from May to September, 2005, in Jaboticabal, São Paulo State, Brazil, in a completely randomized block design, with split-plots. The hydroponic systems were assigned to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 11 publications
0
14
2
8
Order By: Relevance
“…The results for NMP obtained in this study are higher than those reported by Tierno et al (2014), 12.5 NMP for the cultivar Monalisa, and lower than those observed by Factor et al (2007), 40.3 and 46.6 NMP for ' Ágata' and Asterix cultivars, respectively, both in aeroponics system. It is noteworthy, however, that the aeroponics system of this research is larger than the prototype described by Factor et al (2007) and, therefore, closer to the commercial systems used and feasible to be adopted by the productive sector without many adaptations.…”
Section: Plant Densitycontrasting
confidence: 84%
See 2 more Smart Citations
“…The results for NMP obtained in this study are higher than those reported by Tierno et al (2014), 12.5 NMP for the cultivar Monalisa, and lower than those observed by Factor et al (2007), 40.3 and 46.6 NMP for ' Ágata' and Asterix cultivars, respectively, both in aeroponics system. It is noteworthy, however, that the aeroponics system of this research is larger than the prototype described by Factor et al (2007) and, therefore, closer to the commercial systems used and feasible to be adopted by the productive sector without many adaptations.…”
Section: Plant Densitycontrasting
confidence: 84%
“…The aeroponics system adopted was initially described by Factor et al (2007), but adapted for commercial production conditions, according to Calori et al (2014) (Figures 1,2). The system was installed inside a greenhouse The Ágata and Asterix cultivars were used because the tuber shape and skin color are different, facilitating the harvesting and separation in aeroponics, being among the main genotypes currently grown in the , NH 4 + , P, K, Ca, Mg, S, Fe, Zn, Mn, B, Cu, and Mo, respectively, and EC of approximately 2.0 dS•m −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average diameter of tubers was 3.7 cm, a result close but lightly superior from those from Factor et al (2007): 3.0 cm, recorded for sprouts planted in a hydroponic system. On the present work, an average of 3.0 tubers were produced per plant, an amount inferior of that observed by Silva et al (2006): 4.4 tubers per plant grown on different substrate soil mix under protected cultivation system.…”
Section: Summer Protective Cultivation Of Sproutsmentioning
confidence: 42%
“…According to Factor (2007), the hydroponic system can be classified as open (after application, the nutrient solution is not reused) or closed (the nutrient solution is recovered, replenished and recycled). In the hydroponic cultivation, roots received a balanced nutrient solution that contains water and all nutrients necessary for plant development (Barbieri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%